Persuasion in contemporary homily: The case of integrating function - Álvarez-Rosa, Carmen Vanesa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article deals with the analysis of religious argumentation, specifically, in persuasion in contemporary preaching, through the recognition and quantification of pragmalinguistic mechanisms that favor the integration of the listener in the discourse of the religious speaker. The examined corpus consists of 50 oral homilies recorded in the first decade of the 21st century. The results indicate that the most of these mechanisms has a similar incidence in both in adults and children homilies, except for interactive formulas and the recurrence of popular knowledge in which the difference is evident. Therefore, these conclusions shed light on what is dictated by today’s homiletic theory, which states that “you have to approach the parishioner” but does not say how.